Efficacy of acupuncture in ameliorating anxiety in Parkinson's disease: a systematic review and meta-analysis with trial sequential analysis - Wu, Zhennan; Liu, Chang; Chan, Vickie; Wu, Xiaofeng; Huang, Fan; Guo, Zining; Liu, Wenhao; Lu, Liming; Xu, Nenggui (Frontiers in Aging Neuroscience, 2024)
BackgroundAlthough numerous studies have explored acupuncture for alleviating Parkinson's disease (PD) symptoms, specific methods focusing on reducing anxiety in these patients are lacking. Preliminary research indicates that acupuncture may improve anxiety in patients with Parkinson's; however, high-quality evidence is lacking. Therefore, we conducted a meta-analysis and trial sequential analysis (TSA) to assess the efficacy of acupuncture in managing anxiety symptoms in PD.MethodsWe systematically searched eight databases for randomized controlled trials (RCTs) evaluating the efficacy of acupuncture for the treatment of anxiety in patients with PD. Primary outcomes were measured using the Hamilton Anxiety Scale (HAMA) and the Self-Rating Anxiety Scale (SAS). Secondary outcomes included the Parkinson's Disease Questionnaire-39 (PDQ-39) and the Unified Parkinson's Disease Rating Scale (UPDRS). Risk of bias was assessed using the Cochrane RoB 2.0 tool, and certainty of evidence was assessed using the GRADE system. The Trial Sequential Analysis (TSA) was used to assess the sufficiency of the evidence.ResultsOur meta-analysis included 14 studies. The Manual acupuncture (MA) + routine drug treatment (RDT) group improved more than the RDT alone group. MA was more effective than sham acupuncture. MA+ traditional Chinese medicine (TCM) was also more effective than TCM. Auricular therapy (AT) was not as effective as control therapy (CT). The Electroacupuncture (EA) + routine drug treatment (RDT) group was not as effective as RDT. PDQ-39 and UPDRS subgroup analysis showed that the acupuncture group had better clinical efficacy than CT. The GRADE assessment rated the overall certainty of evidence for anxiety outcomes as low, PDQ-39 as very low and UPDRS as low. TSA results indicate insufficient evidence; further high-quality RCTs are needed to substantiate these findings.ConclusionOur analysis suggests that MA combined with RDT may help ameliorate anxiety in PD patients, although the evidence is weak due to low quality RCTs. EA and AT showed no significant effects, highlighting the need for more rigorous studies with better controls and longer follow-up. The potential of acupuncture for PD-related anxiety should be considered with caution until stronger evidence becomes available.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/.